2003
DOI: 10.2460/javma.2003.223.1283
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter case-control study of risk factors associated with development of vaccine-associated sarcomas in cats

Abstract: Findings do not support the hypotheses that specific brands or types of vaccine within antigen class, vaccine practices such as reuse of syringes, concomitant viral infection, history of trauma, or residence either increase or decrease the risk of vaccine-associated sarcoma formation in cats. There was evidence to suggest that certain long-acting injectable medications may also be associated with sarcoma formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
0
22

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(134 citation statements)
references
References 6 publications
1
111
0
22
Order By: Relevance
“…Vaccinations and injections have been found to lead to sarcomas in cats (Kass et al 2003), dogs (Vascellari et al 2003), and ferrets (Munday et al 2003). In humans, there are a number of reports of pacemaker implantation site malignancy that have involved both sarcomas and carcinomas (Bhandarkar et al 1993;Biran et al 1979;Carpentier et al 2000;Fraedrich et al 1984;Okamoto et al 2010), and similarly, one of 104 dogs with pacemaker implantation is reported to have developed fibrosarcoma at the pacemaker generator site, thirty months after implantation (Johnson et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Vaccinations and injections have been found to lead to sarcomas in cats (Kass et al 2003), dogs (Vascellari et al 2003), and ferrets (Munday et al 2003). In humans, there are a number of reports of pacemaker implantation site malignancy that have involved both sarcomas and carcinomas (Bhandarkar et al 1993;Biran et al 1979;Carpentier et al 2000;Fraedrich et al 1984;Okamoto et al 2010), and similarly, one of 104 dogs with pacemaker implantation is reported to have developed fibrosarcoma at the pacemaker generator site, thirty months after implantation (Johnson et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Στόχος είναι η διευκόλυνση της χειρουργικής αφαί ρεσης πιθανού μετεμβολιακού σαρκώματος. Και οι δύο επιστημονικοί φορείς συνιστούν την αποφυγή έγχυσης των εμβολίων στο ακρώμιο (δύσκολη έως αδύνατη η χειρουργική εξαίρεση των σαρκωμάτων) και τη χορήγηση του κάθε εμβολίου σε διαφορετικό σημείο (στον ίδιο ή σε διαφορετικό χρόνο), για να μειωθεί η πιθανότητα εμφάνισης σαρκώματος (Kass et al 2003).…”
Section: σε ποιο σημείο και πώς πρέπει να γίνονται τα εμβό λια στη γάτα;unclassified
“…Both vaccine types contain aluminum as adjuvant [3,4] that is capable to trigger a chronic infl ammation (i.e., granulomatous reaction) at the site of vaccination [4,5]. However, some reports demonstrated no signifi cant difference in the incidence of sarcomas with regard to vaccines with or without adjuvant materials [4,6]. The prevalence of FISS in vaccinated subjects range from 1/1.000 to 1/10.000 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…FISS are regularly occurring in 10 years old subjects (average age), with some peaks in 6-7 and 10-11 years old cats, respectively. A slightly higher incidence was noticed in females compared to males; no breed predisposition was observed [4,6,9,10].…”
Section: Introductionmentioning
confidence: 99%